Topographic indices and ERA5-Land data to describe soil moisture variability in a Central European beech forest - Marian Schönauer; Stephen B. Asabere; Daniela Sauer; Simon Drollinger (Journal of Hydrology: Regional Studies)
Study region: Temperate beech forest in central Germany’s low mountain range Study focus: Soil moisture is essential for ecosystem functioning, influencing hydrological, biological, and biogeochemical processes. It regulates water, energy, and carbon cycles, supporting ecosystem organization, biodiversity, and vegetation resilience. However, climate change and human activities increasingly disrupt soil moisture dynamics, altering spatio-temporal variability due to altered precipitation, rising temperatures, and droughts, making prediction attempts a challenge. This study examines a temperate beech forest in central Germany’s low mountain range, aiming to: (1) analyse spatio-temporal variations in soil moisture and temperature, (2) assess correlations with topographic indices across seasons, and (3) validate ERA5-Land retrievals. We employed 62 automatic sensors and manual measurements at 236 sites within a 900 × 600 m area. Field data were merged with ERA5-Land reanalysis and topographic indices, including depth-to-water and topographic position indices, to assess their performance in predicting soil water content spatial patterns. New hydrological insights for the region: Temporal variation exceeded spatial variation by 3.60–3.68 times. While soil moisture was associated with mesorelief (topographic position index), the correlation was weak. Flow accumulation-based indices were ineffective in capturing spatial soil moisture variation and failed to model spatio-temporal variability. This suggests that model results need to be reconsidered, and suitable indices developed. Insights from this study contribute to improving soil–vegetation–atmosphere models and support sustainable forest management in a changing climate.